2012
DOI: 10.1371/journal.pone.0032967
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Resistance in Vagal Afferent Neurons Inhibits Cholecystokinin Signaling and Satiation in Diet Induced Obese Rats

Abstract: Background and AimsThe gastrointestinal hormone cholecystokinin (CCK) plays an important role in regulating meal size and duration by activating CCK1 receptors on vagal afferent neurons (VAN). Leptin enhances CCK signaling in VAN via an early growth response 1 (EGR1) dependent pathway thereby increasing their sensitivity to CCK. In response to a chronic ingestion of a high fat diet, VAN develop leptin resistance and the satiating effects of CCK are reduced. We tested the hypothesis that leptin resistance in VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
137
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(148 citation statements)
references
References 46 publications
9
137
1
1
Order By: Relevance
“…Moreover, recently it has been shown that leptin resistance within vagal afferents reduces the sensitivity to CCK receptormediated effects [22]. Furthermore, the beneficial effects of (pGlu-Gln)-CCK-8 were less obvious in leptin-deficient ob/ob mice than in high-fat-fed mice [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recently it has been shown that leptin resistance within vagal afferents reduces the sensitivity to CCK receptormediated effects [22]. Furthermore, the beneficial effects of (pGlu-Gln)-CCK-8 were less obvious in leptin-deficient ob/ob mice than in high-fat-fed mice [7].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, leptin and CCK may potentiate their own effects by cross-stimulating their secretion. Furthermore, leptin has recently been shown to play a role in modulating the sensitivity of vagal afferents to CCK [22].…”
Section: Introductionmentioning
confidence: 99%
“…Egr1 has been observed to stimulate CART expression in certain types of neurons (17,23). CART peptides are widely distributed in the CNS and are known to suppress food intake (24,25) and stimulate Fos expression in a number of brain areas when administered centrally (26,27). Leptin-induced Egr1 expression has been shown to increase the sensitivity of vagal afferent neurons to CCK, thereby inhibiting food intake (17,27).…”
Section: Disscussionmentioning
confidence: 99%
“…CART peptides are widely distributed in the CNS and are known to suppress food intake (24,25) and stimulate Fos expression in a number of brain areas when administered centrally (26,27). Leptin-induced Egr1 expression has been shown to increase the sensitivity of vagal afferent neurons to CCK, thereby inhibiting food intake (17,27). Therefore, it was suggested that Egr1-induced CART expression and hypersensitivity to CCK was responsible, at least partially, for the anorexia phenotype in ARP neuron-ablated mice, although functional analysis of the ARP neural circuitry is required to test this hypothesis.…”
Section: Disscussionmentioning
confidence: 99%
“…In vitro, leptin and CCK synergistically increase phosphorylated STAT3 production in the nodose ganglion, which contains the cell bodies of the vagal afferent neurons (20). Other studies have reported that CCK interacts with leptin at the level of the vagal afferent neurons to control the function of early growth response factor 1 (8,9). However, the molecular mechanisms of CCK and leptin interaction in the hypothalamus have not been fully elucidated.…”
mentioning
confidence: 99%